Production of Isolated Giant Unilamellar Vesicles under High Salt Concentrations - Stein, Hannah; Spindler, Susann; Bonakdar, Navid; Wang, Chun; Sandoghdar, Vahid (Frontiers in Physiology, 2017)
The cell membrane forms a dynamic and complex barrier between the living cell and its environment. However, its in-vivo studies are difficult because it consists of a high variety of lipids and proteins and is continuously reorganized by the cell. Therefore, membrane model systems with precisely controlled composition are used to investigate fundamental interactions of membrane components under well-defined conditions. Giant unilamellar vesicles (GUVs) offer a powerful model system for the cell membrane, but many previous studies have been performed in unphysiologically low ionic strength solutions which might lead to altered membrane properties, protein stability and lipid-protein interaction. In the present work, we give an overview of the existing methods for GUV production and present our efforts on forming single, free floating vesicles up to several tens of µm in diameter and at high yield in various buffer solutions with physiological ionic strength and pH.